State of the world, 1995 : a Worldwatch Institute report on progress toward a sustainable society - Brown, Lester R. (New York : Norton, 1995)
"Presents evidence of the birth of an entirely new economy, an environmental revolution that may be as sweeping as the Industrial Revolution that put us on our present unsustainable course. The authors argue that, far from being too costly to consider, the transition to an environmentally sustainable economy represents the greatest investment opportunity in history."--Back cover.
Includes bibliographical references and index.
Keywords: Desarrollo sostenible; Política ambiental